(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, according to the degree of erosion of these soils, the change in the amount of carbonate and gypsum in the soil, the increase in their alkalinity with the increase in carbonate content, and the increase in their buffering capacity for acids and sour environments. In addition, information is given on the role of calcium and magnesium carbonates in the composition of the soil absorbent complex, the differentiation of carbonates and gypsum in these soils, and carbonate minerals that are widely distributed in the soil.